Inhibition of Fibrin Polymerization by Serum Amyloid P Component and Heparin - Meyer, Keith; Smith, Robert; Williams, Eliot C (Thrombosis and Haemostasis, 1987)
The effects of serum amyloid P component (SAP) and heparin on the thrombin-catalyzed formation of polymeric fibrin from purified fibrinogen were examined using a turbidometric method to quantify fibrin polymerization. SAP and heparin acted synergistically to inhibit the lateral aggregation of fibrin fibrils, resulting in the formation of fibrils with a smaller mass to length ratio. Heparin did not enhance the incorporation of SAP into fibrin clots, and the effect of heparin and SAP did not seem to be related to inhibition of thrombin or of fibrinopeptide release. The evidence suggests that a soluble complex of SAP and heparin inhibits fibrin polymerization.
Keywords: Amyloid P component; Heparin; Fibrin polymerization